2017
DOI: 10.7705/biomedica.v37i3.3395
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of intestinal polyparasitism in a community of the Colombian Amazon region

Abstract: Several intestinal polyparasitism profiles were found, although in most cases fewer than six parasites were involved. Better prevalence estimations and identification of determinant factors will allow to priorize and direct resources to control these infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
3
1
5
Order By: Relevance
“…In an Argentine study, a frequency of 54% 22 was reported. In Cali, a frequency of 52.1% 23 , and in another study in the Amazon region, a frequency of 84% 24 , while in the present study it was 37.9%.…”
Section: Discusioncontrasting
confidence: 51%
“…In an Argentine study, a frequency of 54% 22 was reported. In Cali, a frequency of 52.1% 23 , and in another study in the Amazon region, a frequency of 84% 24 , while in the present study it was 37.9%.…”
Section: Discusioncontrasting
confidence: 51%
“…infection suggests multiple sources of infection. Mixed parasitic infections are highly predicted in rural areas due to the presence of multiple risk factors, as has been previously documented [44][45][46][47] . Consumption of contaminated water and unwashed vegetables, lack of fingernail trimming and hand washing, children playing in the dirt, barefoot walking, low socioeconomic status, lack of sanitation, and large numbers of family members sharing a single room have all been observed among the residents of West Ismailia 27,31,48,49 .…”
Section: Discussionmentioning
confidence: 70%
“…Infection by multiple parasite species confers increased susceptibility to other infections [46], and qPCR allows greater sensitivity in the identification of polyparasitism, making it a useful tool for the evaluation of public health interventions [47]. In Colombia, studies of polyparasitism have been carried out in indigenous communities and found that both helminths and protozoa were involved [48].…”
Section: Discussionmentioning
confidence: 99%